2007
DOI: 10.1063/1.2787151
|View full text |Cite
|
Sign up to set email alerts
|

Incongruent reaction of Cu–(InGa) intermetallic precursors in H2Se and H2S

Abstract: The reaction pathways to form Cu(InGa)Se2 or Cu(InGa)S2 films at 450°C from metallic precursors were evaluated by reacting Cu–In–Ga films in H2Se or H2S for 10, 30, or 90min and characterizing the phase composition of the resulting films. A starting composition comprising Cu9(In0.64Ga0.36)4 and In phases was detected by x-ray diffraction in Cu–Ga–In precursors annealed at 450°C in an Ar atmosphere. When the precursors were reacted in H2Se, a graded Cu(InGa)Se2 film was formed with a Ga-rich composition and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 21 publications
13
66
0
Order By: Relevance
“…This difference between In/(CuGaþIn) and CuGa/In is related to Ga content in CIG precursors. This mixed peak is believed to be a Cu 9 In 4 -Cu 9 Ga 4 alloy with Ga/(InþGa) ratio [22]. From the XRD results, we can confirm the texture formation of CIG precursor layers as determined from composition of CIG precursors [23].…”
Section: Xrd Studysupporting
confidence: 71%
See 1 more Smart Citation
“…This difference between In/(CuGaþIn) and CuGa/In is related to Ga content in CIG precursors. This mixed peak is believed to be a Cu 9 In 4 -Cu 9 Ga 4 alloy with Ga/(InþGa) ratio [22]. From the XRD results, we can confirm the texture formation of CIG precursor layers as determined from composition of CIG precursors [23].…”
Section: Xrd Studysupporting
confidence: 71%
“…Also, it can consider that the Ga atoms are diffused toward interface between Mo film and CIGS absorption layer. Se preferentially reacts with In during the selenization process, because reaction energy of In is lower than Ga for Se [22]. The elemental composition distributions onto the surface and into the depth of the surface demonstrate the diffusion behavior of Ga atoms from composition profile by XPS, EDS and SIMS analysis.…”
Section: Xrd Studymentioning
confidence: 95%
“…The nodules are Cu and Ga rich compared to the overall composition, while the background is predominantly In. The similar precursor structure was previously reported [4].…”
Section: Precursorssupporting
confidence: 71%
“…However, it is widely observed that Ga migrates away from the junction to the Mo back contact [2,3,4]. This backcontact Ga accumulation prevents the increase in bandgap near the junction that is needed for the achievement of high voltage solar cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation